Comparison of performance of one-color and two-color gene-expression analyses in predicting clinical endpoints of neuroblastoma patients - Oberthür, Carl André; Juraeva, D.; Li, L.; Kahlert, Y.; Westermann, Frank; Eils, Roland; Berthold, F.; Shi, L.; Wolfinger, R. D.; Fischer, M.; Brors, Benedikt (The pharmacogenomics journal, 2010)
Microarray-based prediction of clinical endpoints may be performed using either a one-color approach reflecting mRNA abundance in absolute intensity values or a two-color approach yielding ratios of fluorescent intensities. In this study, as part of the MAQC-II project, we systematically compared the classification performance resulting from one- and two-color gene-expression profiles of 478 neuroblastoma samples. In total, 196 classification models were applied to these measurements to predict four clinical endpoints, and classification performances were compared in terms of accuracy, area under the curve, Matthews correlation coefficient and root mean-squared error. Whereas prediction performance varied with distinct clinical endpoints and classification models, equivalent performance metrics were observed for one- and two-color measurements in both internal and external validation. Furthermore, overlap of selected signature genes correlated inversely with endpoint prediction difficulty. In summary, our data strongly substantiate that the choice of platform is not a primary factor for successful gene expression based-prediction of clinical endpoints.
Gesehen am 26.05.2023